2014
DOI: 10.4049/jimmunol.1302805
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Alterations of Epitope Production by HIV Protease Inhibitors

Abstract: Antigen processing by intracellular proteases and peptidases and epitope presentation are critical for recognition of pathogen-infected cells by CD8+ T lymphocytes. First generation HIV protease inhibitors (PIs) alter proteasome activity, but the effect of first or second generation PIs on other cellular peptidases, the underlying mechanism and impact on antigen processing and epitope presentation to CTL are still unknown. Here we demonstrate that several HIV PIs altered not only proteasome but also aminopepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 78 publications
2
40
0
Order By: Relevance
“…The degradation was stopped with 2.5μL of 100% formic acid and peptide fragments were purified by 5% trichloroacetic acid precipitation. Degradation peptides were identified by in-house MS as previously described (8, 19). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation was stopped with 2.5μL of 100% formic acid and peptide fragments were purified by 5% trichloroacetic acid precipitation. Degradation peptides were identified by in-house MS as previously described (8, 19). …”
Section: Methodsmentioning
confidence: 99%
“…In mice infected with lymphocytic choriomeningitis virus (LCMV) and treated with RTV, cytotoxic T cell (CTL) responses against LCMV epitopes were changed (6). We previously showed that HIV PIs altered proteasome and aminopeptidase activities in primary human cells, modified HIV protein degradation patterns in a sequence-dependent manner, epitope production and presentation, altering CTL responses (8). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure peptides (2 nmol) were digested at 37°C for 30 to 240 min with 15 g of cytosolic extracts of matching cells (293T cells, B cells, and primary CD4 T cells) (20). The degradation was stopped with 2.5 l of 100% formic acid, and peptide fragments were purified by the use of 5% trichloroacetic acid (TCA) precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…The degradation was stopped with 2.5 l of 100% formic acid, and peptide fragments were purified by the use of 5% trichloroacetic acid (TCA) precipitation. Degradation peptides generated in 2 to 3 independent degradation experiments were identified by in-house LC/MS-MS as previously described (20,21,28).…”
Section: Methodsmentioning
confidence: 99%